Building services handbook - Hall, F. (Fred) (2017)
This handbook summarises in diagrams and brief explanations all elements of building services. It is a reference for professionals and students on advanced vocational courses and has been updated in line with the latest revised Building Regulations.
Previous edition: published as by Fred Hall and Roger Greeno. 2015.
Includes index.
Keywords: Building -- Handbooks, manuals, etc; Buildings -- Environmental engineering; Buildings -- Mechanical equipment -- Installation -- Handbooks, manuals, etc